2009
DOI: 10.1158/1535-7163.mct-08-0596
|View full text |Cite
|
Sign up to set email alerts
|

In vivoactivity of novel capecitabine regimens alone and with bevacizumab and oxaliplatin in colorectal cancer xenograft models

Abstract: Modifying the capecitabine dosing schedule from 14 days on, 7 days off (14/7) to 7 days on, 7 days off (7/7) may enable higher doses and improved antitumor efficacy in colorectal cancer xenografts. Capecitabine 14/7 (267 or 400 mg/kg) and 7/7 (467 or 700 mg/kg) schedules in doublet and triplet combinations with optimally dosed bevacizumab (5 mg/kg) and oxaliplatin (6.7 mg/kg) were studied in female athymic nude mice bearing HT29 colorectal xenografts. Additional studies of suboptimally dosed bevacizumab (2.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Such efficacy is likely due to a failure in their ability to recruit a vasculature and enable these isolated cells to progress and grow to a size that will be detectable by conventional computed tomography scans. Such residual disease models have been used to study the effect of prolonged VEGF blockade following chemotherapy (43)(44)(45)(46) and have shown that anti-VEGF therapy primarily functions to delay rather than prevent tumor regrowth. However, we believe that these studies are the first to show that in some models of residual tumor burden, prolonged anti-VEGF therapy can prevent tumor regrowth for prolonged periods.…”
Section: Discussionmentioning
confidence: 99%
“…Such efficacy is likely due to a failure in their ability to recruit a vasculature and enable these isolated cells to progress and grow to a size that will be detectable by conventional computed tomography scans. Such residual disease models have been used to study the effect of prolonged VEGF blockade following chemotherapy (43)(44)(45)(46) and have shown that anti-VEGF therapy primarily functions to delay rather than prevent tumor regrowth. However, we believe that these studies are the first to show that in some models of residual tumor burden, prolonged anti-VEGF therapy can prevent tumor regrowth for prolonged periods.…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported that parenterally given CSF-1 antibody and CSF-1 antisense oligonucleotides reduced tumor-associated endothelial cell proliferation together with an ∼50% growth suppression of mammary and colon carcinoma xenografts accompanied by substantial extensions in survival (10)(11)(12). Although tumors continued to grow in the presence of CSF-1/CSF-1R inhibition, this was also true of similar xenografts after treatment with bevacizumab, a vascular endothelial growth factor antibody in current clinical use to treat breast and colon cancer in combination with standard therapy (36). Of note, survival benefits provided by CSF-1 antibody was more (Table 2).…”
Section: Molecular Cancer Therapeuticsmentioning
confidence: 91%
“…MK-2206 (Selleck Inc.) was formulated in 30% Captisol (CyDex Pharmaceuticals). Capecitabine (Xeloda; Roche Laboratories) suspensions and clinical grade bevacizumab (Avastin; Genentech, Inc.) were prepared as previously described (21). Irinotecan (Camptosar; Pfizer) was provided in a stock sterile saline solution of 20 mg/mL, which was diluted as required with sterile saline.…”
Section: Test Agents For In Vivo Studiesmentioning
confidence: 99%
“…4A) over 3 weeks. The 400 and 700 mg/kg doses correspond to the previously determined maximum tolerated dose (MTD) for the 14-and 7-day schedules, respectively (21). Bevacizumab (5 mg/kg) was dosed intraperitoneally using a sterile 1-mL syringe and 26-gauge needle (0.2 mL/animal, twice a week) on a Tuesday/Friday schedule.…”
Section: Vemurafenib/erlotinib Combination Studiesmentioning
confidence: 99%